Bioconversion of lignocellulose and simultaneous production of cellulase, ligninase and bioflocculants by Alcaligenes faecalis-X3. (March 2020) - Chen, Shuli; Sun, Su; Zhong, Chunying; Wang, Tongfei; Zhang, Yi; Zhou, Jiangang
Graphical abstract: Highlights: A novel bioflocculant-producing bacterium was isolated from ramie biodegumming wastewater. The bacterium can secrete ligninase and cellulase through direct conversion of ramie biomass. The ramie biodegumming wastewater was utilized to prepare enzymes and bioflocculants. The bioflocculants'production was closely related to the enzymatic activities. Abstract: Lignocelluloses have been used as carbon sources for bioflocculant production. However, the low bioconversion efficiency of lignocellulose to bioflocculants is a major challenge. In this study, a lignocellulolytic strain of Alcaligenes faecalis -X3 was cultivated in ramie bio-degumming wastewater. Optimal production of ligninase, cellulase and bioflocculants (MBF-X3) was evaluated. The highest activity of MBF-X3 under the optimal conditions of pH 6.0 at 48 h of fermentation was 95.44%, with the maximum production of ligninase and cellulase (0.27 and 0.12 U/mL, respectively). The crude ligninase and cellulase had optimum activities at pH 5.0 and 40 °C and pH 6.0 and 50 °C, respectively. The cellulase activity was increased by Mn 2+, Ca 2+, Zn 2+, and Mg 2+ at 1 mM. The ligninase activity was significantly enhanced in the presence of Zn 2+ at 10 mM. The flocculating activity of MBF-X3 was not changed by the addition of any metal cation. The results demonstrated that A. faecalis possesses an excellent enzyme system for the efficient bioconversion of lignocellulose into MBF-X3. Additionally, MBF-X3 has a high flocculating efficiency of Disperse Blue-2BLN (85.7%) at a dose of 1.0 g/L.